CAR-T Cell–Mediated B-Cell Depletion in Central Nervous System Autoimmunity. Issue 2 (19th March 2023) - Gupta, Sasha; Simic, Milos; Sagan, Sharon A.; Shepherd, Chanelle; Duecker, Jason; Sobel, Raymond A.; Dandekar, Ravi; Wu, Gregory F.; Wu, Wesley; Pak, John E.; Hauser, Stephen L.; Lim, Wendell; et al.
Abstract : Background and Objectives: Anti-CD20 monoclonal antibody (mAb) B-cell depletion is a remarkably successful multiple sclerosis (MS) treatment. Chimeric antigen receptor (CAR)-T cells, which target antigens in a non-major histocompatibility complex (MHC)–restricted manner, can penetrate tissues more thoroughly than mAbs. However, a previous study indicated that anti-CD19 CAR-T cells can paradoxically exacerbate experimental autoimmune encephalomyelitis (EAE) disease. We tested anti-CD19 CAR-T cells in a B-cell–dependent EAE model that is responsive to anti-CD20 B-cell depletion similar to the clinical benefit of anti-CD20 mAb treatment in MS. Methods: Anti-CD19 CAR-T cells or control cells that overexpressed green fluorescent protein were transferred into C57BL/6 mice pretreated with cyclophosphamide (Cy). Mice were immunized with recombinant human (rh) myelin oligodendrocyte protein (MOG), which causes EAE in a B-cell–dependent manner. Mice were evaluated for B-cell depletion, clinical and histologic signs of EAE, and immune modulation. Results: Clinical scores and lymphocyte infiltration were reduced in mice treated with either anti-CD19 CAR-T cells with Cy or control cells with Cy, but not with Cy alone. B-cell depletion was observed in peripheral lymphoid tissue and in the CNS of mice treated with anti-CD19 CAR-T cells with Cy pretreatment. Th1 or Th17 populations did not differ in anti-CD19 CAR-T cell, control cell-treated animals, or Cy alone. Discussion: In contrast to previous data showing that anti-CD19 CAR-T cell treatment exacerbated EAE, we observed that anti-CD19 CAR-T cells ameliorated EAE. In addition, anti-CD19 CAR-T cells thoroughly depleted B cells in peripheral tissues and in the CNS. However, the clinical benefit occurred independently of antigen specificity or B-cell depletion.